Reflections on the concept of Sustainable Tourism and its integration in the current Ecuadorian sociopolitical context - Hernanz, Iris Martín (2013)
Last decades Sustainable Tourism, has been wide acceptance in international, regional and national politics. However, in most cases there has been few reflec- tions on what should be the approach to follow, and a definition of its objectives and values. This article is a reflection on Sustainable Tourism, based on the study of the evolution of sustainable development, the theoretical analysis of the concept and a review of international documents and their main contributions. It also discusses the integration of Sustainable Tourism in Ecuador's current social-political context defined by the Constitution of 2008, the Plan Nacional del Buen Vivir and, specifically, the Plan estratégico de desarrollo de turismo sostenible para Ecuador.